2018
DOI: 10.1038/s41598-018-25202-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective rapid prototyping and assembly of poly(methyl methacrylate) microfluidic devices

Abstract: The difficulty in translating conventional microfluidics from laboratory prototypes to commercial products has shifted research efforts towards thermoplastic materials for their higher translational potential and amenability to industrial manufacturing. Here, we present an accessible method to fabricate and assemble polymethyl methacrylate (PMMA) microfluidic devices in a “mask-less” and cost-effective manner that can be applied to manufacture a wide range of designs due to its versatility. Laser micromachinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 40 publications
2
68
0
Order By: Relevance
“…Maintaining solvation evaporation at a lower temperature offered better controllability of the polishing process by tuning evaporation times. In a related study, Matellan et al used acetone to polish a laser-engraved microchannel at 30 • C. They revealed that evaporation at lower temperatures can avoid the generation of visible cracks during polishing [35]. Thus, we chose 40 • C as our solvent temperature and tested different solvent evaporation times (1, 2, 3, 4, 5, and 6 min) to evaluate changes in surface roughness during chemical polishing.…”
Section: Surface Polishing Of Microchannels and Micromoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining solvation evaporation at a lower temperature offered better controllability of the polishing process by tuning evaporation times. In a related study, Matellan et al used acetone to polish a laser-engraved microchannel at 30 • C. They revealed that evaporation at lower temperatures can avoid the generation of visible cracks during polishing [35]. Thus, we chose 40 • C as our solvent temperature and tested different solvent evaporation times (1, 2, 3, 4, 5, and 6 min) to evaluate changes in surface roughness during chemical polishing.…”
Section: Surface Polishing Of Microchannels and Micromoldsmentioning
confidence: 99%
“…Several approaches have been introduced to smooth the surface after milling. For example, Matellan et al use acetone vapor treatment to smooth the PMMA surface as a cost-effective rapid prototyping method [35] to generate the microfluidic device; or they use cryogenic cooling to polish the acrylic-based polymer for optical lens application [36]. In addition to these approaches, abrasive polishing tools are commonly used to polish plastic parts in large scale [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in demand for disposable microfluidic devices in near-patient settings, cost-effective technologies, such as soft lithography, for developing polymeric micro and nano-chips have increased in the past two decades [102,103]. Laser-based micromachining techniques are also used for fabricating low-cost devices from thermoplastics [104]. In the past few years, µPADs, also termed as microfluidic paper-based analytical devices, have been gaining popularity because of their convenient accessibility and affordability.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…Rapid prototyping of thermoplastics can be also be carried out by laser micromachining. This technology can produce a number of microfluidic devices of different designs without the requirement for master moulds [104]. A laser beam projected towards a given substrate such as thermoplastic, metal, polymer, ceramic or glass creates a cavity either photo-chemically or photo-thermally or by the combination of both.…”
Section: Injection Moulding and Laser Processingmentioning
confidence: 99%
“…Although the operational conditions of both injection molding and hot embossing processes are well established in the industries, during the large‐scale fabrication it is impracticable to make changes in the device design to meet the experimental specificities that arise during research using microfluidic chips. Therefore, many research groups have developed alternative processes for manufacturing PMMA devices, such as solvent imprinting [17], soft molding [18–20], hot embossing with milled metal masters [21], laser ablation [22–24], metal wire removal [25], and UV‐photopolymerization [26,27]. Among these methods, CNC milling [21,28] and laser ablation [22–24] have provided the best results without needing to be combined with conventional photolithographic techniques [17,20,26,27,29,30].…”
Section: Introductionmentioning
confidence: 99%